The Competitiveness of National Solar Modules in Residential Market: Perspective of EPC Companies - Dwi Nurma Heitasari; Ibnu Lukman Pratama; Andian Ari Istiningrum; Qonita Hana Insyira (Faculty of Economics and Business Udayana University, 2026)
Indonesia has a significant potential for silica sand. Yet, the utilization of solar energy is less than that of fossil fuels, while the conversion of renewable energy is becoming increasingly prevalent. On a residential scale, as the largest consumer of electricity, the use of solar modules has not yet reached the scale targeted by the government, in part due to the preferences of Engineering, Procurement, and Construction (EPC) companies, which assemble solar modules, in choosing imported solar modules over domestic solar modules, which are associated with residential market expectations, resulted in the low of domestic component level value. The objective of this study is to determine the considerations of EPC companies when comparing solar modules. The analysis employs quantitative and qualitative research using Expert Choice Software through the Analytical Hierarchy Process method. The respondents came from industrial experts of solar module EPC companies in Indonesia. The study indicates that cost criteria exert the most significant influence on the selection of solar modules. It is necessary to enhance product quality criteria by increasing research and development to reduce prices and improve the competitiveness of national products.